THU0071 Muscle lipotoxicity on sarcopenia development in a model of collagen-induced arthritis. (12th June 2018) - Vial, G.; Pinel, A.; Bechet, D.; Wauquier, F.; Wittrant, Y.; Chevenet, C.; Soubrier, M.; Tournadre, A.; Capel, F.
Abstract : Background: Alterations of body composition in Rheumatoid arthritis (RA) may contribute to the development of cardiometabolic disorders. RA patients have a decrease in muscle mass with a preserved or increased fat mass, notably accumulation of ectopic fat in the muscles, witch define the sarcopenic obesity. The mechanisms leading to this sarcopenic obesity phenotype remain poorly understood. Accumulation of intramuscular lipids and the formation of lipotoxic compounds may affect intracellular signalling pathways and energy production, alter protein synthesis and thus promote sarcopenia. Objectives: Our objective was to determine if muscular lipotoxicity promotes the development of sarcopenia in joint inflammatory condition, using rats with collagen-induced arthritis. Methods: Male Sprague Dawley rats were divided into a control group (CO, n=12) and a collagen-induced arthritis group (CIA, n=11). After 5 weeks, hind leg muscles and epididymal adipose tissue were removed. Tissues were weighed at sacrifice and stored for histological analyses and evaluation of mitochondrial function, lipotoxicity, protein and gene expression levels. Statistical analyses were performed with t-test. Results: Animals, adipose tissue and muscle weights tended to be lower in the CIA group. Only EDL muscle weight was significantly lower in the CIA group (p=0.05). Muscle histological analyses showed larger CSA (cross sectional area) in CO group. In the CIA group we observed a nonhomogeneous distribution of muscle fibre CSA with a predominance of small fibres (figure 1). Mean perimeter and mean diameter were also significantly decrease in CIA group but the shape of fibres remained similar between groups. Furthermore, there was an increased expression of MAFBx (a marker of catabolism) mRNA (40%, p=0.04) in the CIA group, while MyoD (a myogenesis marker) mRNA was decreased by 18% (p=0.01), indicating a catabolic state. Lipid content analysis showed an accumulation of intramuscular TAG (x 1.5, p=0.05), as well as an increased expression of cellular fatty acid transporter FATP1 (about 35%, p=0.01) and mitochondrial fatty acid transporter CPT1b (about 27%, p=0.02). Mitochondrial DNA copy number was decreased by 27% in CIA rats (p=0.01) and complex IV activity of mitochondrial respiratory chain also tended to be reduced in CIA group (−20%, p=0.18). Conclusions: Collagen-induced arthritis induced fibres alterations in skeletal muscle. The association of increased muscle protein catabolism, mitochondrial dysfunction and fatty acid accumulation in skeletal muscle of animals with arthritis supports the hypothesis that lipotoxicity is involved in sarcopenia development during joint inflammation. Disclosure of Interest: None declared